Sorafenib and FH535 in combination act synergistically on hepatocellular carcinoma by targeting cell bioenergetics and mitochondrial function. Issue 6 (June 2017) - Turcios, Lilia; Vilchez, Valery; Acosta, Luis F.; Poyil, Pratheeshkumar; Butterfield, David Allan; Mitov, Mihail; Marti, Francesc; Gedaly, Roberto
Abstract: Treatment of advanced hepatocellular carcinoma (HCC) remains a challenge due to the high tumor heterogeneity. In the present study, we aim to evaluate the impact of the β-catenin inhibitor, FH535, alone or in combination with the Ras/Raf/MAPK inhibitor Sorafenib, on the bioenergetics profiles of the HCC cell lines Huh7 and PLC/PRF/5. Single low-dose treatments with FH535 or Sorafenib promoted different effects on mitochondrial respiration and glycolysis in a cell type specific manner. However, the combination of these drugs significantly reduced both mitochondrial respiration and glycolytic rates regardless of the HCC cells. The significant changes in mitochondrial respiration observed in cells treated with the Sorafenib-FH535 combination may correspond to differential targeting of ETC complexes and changes in substrate utilization mediated by each drug. Moreover, the bioenergetics changes and the loss of mitochondrial membrane potential that were evidenced by treatment of HCC cells with the combination of FH535 and Sorafenib, preceded the induction of cell apoptosis. Overall, our results demonstrated that Sorafenib-FH535 drug combination induce the disruption of the bioenergetics of HCC by the simultaneous targeting of mitochondrial respiration and glycolytic flux that leads the synergistic effect on inhibition of cell proliferation. These findings support the therapeutic potential of combinatory FH535-Sorafenib treatment of the HCC heterogeneity by the simultaneous targeting of different molecular pathways.